Тематична класифікація детермінологізмів у романі Ю. Андруховича “Московіада” - Куньч, Зоряна; Берендій, Юрій (Видавництво Львівської політехніки, 2020)
The article raises the problem of determinologization of scientific vocabulary. The material of Yurii Andrukhovych’s novel “Moscoviada” reveals the main thematic categories of determinisms which were used in the literary text and clarifies the reasons of the predominance of certain thematic groups. The issues, which are raised in the novel contributed to the involvement of a large group of cultural and artistic determinisms. Using of these terms helps to express the content and adds an expression of a certain emotional color.
Keywords: термін; детермінологізація; художній текст; тематичний розряд; детермінологізм